Perceptions and feelings of end-of-life patients: a look at palliative care - Monteiro, Daiane da Rosa (2020)
Cancer is one of the most complex public health problems today, accounting for millions of deaths per year worldwide. Upon receiving the diagnosis of cancer, the individual is faced with the fragility of his existence and the possibility of death becomes present in his thoughts. Palliative care is characterized by care provided when there is no therapeutic possibility of cure. Associated with this aspect, there is growing concern about the patient's understanding of his illness and treatment. The study aims to know the feelings and perceptions of the cancer patient in palliative care. It is an integrative review, of a qualitative nature, whose analysis will be of an exploratory approach. The study consisted of seven articles selected from the Medline, Pubmed and Scielo databases between 2010 and 2020. The study points out that patients have different feelings and perceptions about their health status, such as: insecurity, loss of dignity, problems with decision making, parental concerns, reduced quality of life and fluctuations in symptoms. Having knowledge about these aspects in such a fragile life span can support new care plans to be made together with the patient and his family network, easing the burden on the disease's prognosis.